Psychological Well-Being of female pastors: The Role of Self-Compassion and Social Support - Hermanoes, Serly Elis; Kristianingsih, Sri Aryanti; Soetjiningsih, Christiana Hari (Kuras Institute, 2024)
This research is a quantitative study which aims to determine self-compassion and social support simultaneously as predictors of psychological well-being in female pastors at the Evangelical Christian Church in Timor (GMIT). Data collection used Ryff's Psychological Well-Being Scale (RPWB), Self-Compassion Scale (SCS), and Revised Multidimensional Scale of Perceived Social Support (RMSPSS) which were distributed by sending questionnaires via Google form to the WhatsApp group and print outs were delivered directly to respondents. The respondents involved in this research were 105 female GMIT priests around Kupang City. The data obtained were analyzed using multiple linear regression techniques with the help of the SPSS 29 program. The results showed that the calculated F value (simultaneous) was 211.423 with p < 0.05, which means self-compassion and social support simultaneously as predictor of psychological well-being of GMIT female priests around Kupang City with a coefficient of determination (R²) of 0.806, meaning the contribution of the influence of self-compassion and social support to psychological well-being is 80.6%.